Efficacy, safety, and optimal use of isoosmolar contrast medium (Iodixanol) in diagnostic and interventional procedures: A Thai multidisciplinary expert meeting report - Chiewvit, Pipat; Charoenvisal, Ching; Tangweerapong, Kampantong; Chandavimol, Mann; Kwankajonwong, Nachakorn; Chadbunchachai, Payia; Thamtorawat, Somrach; Kritsaneepaiboon, Supika; Amto, Surapee; Janpanich, Sureerat; Srisuwan, Tanop; Sukkasem, Warawut; et al. (The ASEAN Journal of Radiology, 2026)
Contrast media are used in clinical practice for diagnostic and therapeutic purposes. To discuss the position of iso-osmolar contrast media (IOCM) in diagnostic and interventional procedures in Thailand, an expert advice meeting, including neurologists, cardiologists, nephrologists, radiologists, radiologic technologists and radiologic nurses, was organized to discuss the use of IOCM and low-osmolar contrast media, in general and in specific risk groups. Topics discussed included acute kidney injury, cardiovascular events, patient discomfort, allergic reactions, and high-risk groups. The experts agreed that IOCM has an overall beneficial safety profile as compared to low-osmolar contrast media. With the use of IOCM, patients have a low risk of allergic reactions, and a reduced risk of contrast-associated acute kidney injury. Moreover, the patient will feel less pain. Therefore, IOCM is considered particularly useful in patients at high risk of acute kidney injury, especially in procedures that involve significant contrast exposure.